2023
DOI: 10.1002/jmv.29025
|View full text |Cite
|
Sign up to set email alerts
|

CREB1 activation promotes human papillomavirus oncogene expression and cervical cancer cell transformation

Abstract: Human papillomaviruses (HPVs) infect the oral and anogenital mucosa and can cause cancer. The high‐risk (HR)‐HPV oncoproteins, E6 and E7, hijack cellular factors to promote cell proliferation, delay differentiation and induce genomic instability, thus predisposing infected cells to malignant transformation. cAMP response element (CRE)‐binding protein 1 (CREB1) is a master transcription factor that can function as a proto‐oncogene, the abnormal activity of which is associated with multiple cancers. However, lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…As we previously demonstrated, miR-203 significantly reduced cell growth and colony formation in HPV+ cervical cancer cells (Fig. 5C-E; (40)).…”
Section: Mir-203 Inhibits the Proliferation Of Hpv+ Cervical Cancer C...supporting
confidence: 81%
See 4 more Smart Citations
“…As we previously demonstrated, miR-203 significantly reduced cell growth and colony formation in HPV+ cervical cancer cells (Fig. 5C-E; (40)).…”
Section: Mir-203 Inhibits the Proliferation Of Hpv+ Cervical Cancer C...supporting
confidence: 81%
“…miRNAs regulate many fundamental cellular functions, such as transcription, post-transcriptional modifications, and signal transduction (54). Data from our lab and others has shown that miR-203a, a well-studied tumour suppressor, is downregulated by HPV E6 and E7 (40,(46)(47)(48). We have previously shown that the targeting of CREB1 is partially responsible for the proliferation defects observed upon miR-203 re-introduction in HPV+ cervical cancer cells (40).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations